2021
DOI: 10.3390/ijerph18094586
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators of Cervical Cancer Screening among Women in Southeast Asia: A Systematic Review

Abstract: In Southeast Asia, cervical cancer is the second most common cancer in women. Low coverage for cervical cancer screening (CCS) becomes a roadblock to disease detection and treatment. Existing reviews on CCS have limited insights into the barriers and facilitators for SEA. Hence, this study aims to identify key barriers and facilitators among women living in SEA. A systematic literature review was conducted on Pubmed, Embase, PsycINFO, CINAHL, and SCOPUS. Primary qualitative and quantitative studies published i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 81 publications
5
36
0
Order By: Relevance
“…Low-risk perception and education status were also relevant, as women with higher education are more aware of how to independently access reliable information on CC [ 23 , 38 , 40 , 47 , 50–52 , 55 , 57 , 58 , 61–63 ]. The significance of education, knowledge and awareness of CC and related screening services is a frequently observed demand-side barrier and facilitator across research on CC screening in LMICs including in Southeast Asia, which affirms the findings of our review [ 12 , 66 ]. However, it also underlines the persistent global focus on women in research as a main source for low CC screening uptake, without contextualising uptake within broader structural issues of the respective health system.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Low-risk perception and education status were also relevant, as women with higher education are more aware of how to independently access reliable information on CC [ 23 , 38 , 40 , 47 , 50–52 , 55 , 57 , 58 , 61–63 ]. The significance of education, knowledge and awareness of CC and related screening services is a frequently observed demand-side barrier and facilitator across research on CC screening in LMICs including in Southeast Asia, which affirms the findings of our review [ 12 , 66 ]. However, it also underlines the persistent global focus on women in research as a main source for low CC screening uptake, without contextualising uptake within broader structural issues of the respective health system.…”
Section: Discussionsupporting
confidence: 87%
“…This pattern is also apparent in the published research on this topic focused on LMICs more generally. The tendency to focus research on individual-based (demand side) factors that prevent was also noted in a recent systematic review of 2021 on barriers and facilitators to CC screening in Southeast Asia [ 12 , 65 , 66 ]. The imbalance in focus of individual behavioural factors has also be observed within other research areas as demonstrated in a recent systematic review on NCDs by Schröders et al (2017) [ 3 ], which noted a focus on risk factors on the individual level for the management of NCDs rather than a more efficient public health approach within Indonesia [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations